Generalized Anxiety in Uninvestigated Dyspepsia Patients: A Single Centre Cross-Sectional Study - Mahbub, Imteaz; Karim, Md Enamul; Hossain, Md Altaf; Rahman Chowdhury, Md Moshfiqur; Appolo, Al Mahmood; Rahim, Sayeda (Medicine Today, 2025)
Introduction: Generalized anxiety is the most common mental disorder worldwide. Psychological stress like anxiety may cause gastrointestinal distress and lead to dyspeptic symptoms. Moreover, dyspepsia especially uninvestigated dyspepsia in turn may cause anxiety among the patients by creating uncertainty about the disease and its future. Objective: To measure anxiety among patients suffering from uninvestigated dyspepsia. Materials and Methods: This study was conducted at the outpatient department of Medical Gastroenterology, Sheikh Russel National Gastroliver Institute and Hospital from December 2023 to May 2024 over six months. A total of 164 patients of uninvestigated dyspepsia patients were enrolled and by dint of GAD-7 validated Bengali questionnaire their generalized anxiety level was measured and categorized. Demographic variables were analyzed by chi square test and correlation with anxiety and number of symptoms was done by Pearson correlation. P value < 0.05 was regarded as statistically significant. Results: One hundred and sixty-four patients with uninvestigated dyspepsia attending the outpatient department of Sheikh Russel National Gastroliver Institute and Hospital from December 2023 to May 2024 were enrolled. Among the patients, 92 patients were female and 72 were male without any significant difference (P = 0.06). The common age group with dyspepsia and anxiety was 18-40 years. The difference with higher age groups was significant (P =0.02). Most participants were service holders or businessman professions without significant differences (P = 0.97). There was a significant positive correlation between anxiety and an increasing number of symptoms of dyspepsia (P = 0.007, r = +.9929). Conclusion: Anxiety and dyspepsia have a positive relationship. Younger age, female sex and stressed professions like service may contribute to dyspepsia. Medicine Today 2025, Vol.37 (1): 57-60